2014
DOI: 10.1063/1.4884835
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of nitinol surfaces oxidized by low-energy ion bombardment

Abstract: We have studied the electronic structure of nitinol exposed to low-energy oxygen-ion bombardment, using x-ray photoemission spectroscopy (XPS) and near-edge x-ray absorption fine structure (NEXAFS) spectroscopy. XPS spectra reveal a gradual transformation of nitinol surfaces into TiO2 with increased dose of implanted oxygen. No oxidation of Ni atoms has been detected. NEXAFS spectra around O K-edge and Ti L2,3-edge, reflecting the element-specific partial density of empty electronic states, exhibit features, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The spectrum from a cleaned Ni reveals one dominant, asymmetric line shape at 852.5 eV and two broad, less intensive satellite lines (plasmon loss peaks) with binding energies (BE) about 3.0 eV and 6.0 eV above the main line. The same XPS spectra have been previously reported from cleaned Ni surfaces in the literature [7,10], supporting our assumption of efficient cleaning of Ni surfaces within the UHV chamber. After oxidation, the XPS spectra become more complex with several new and well-distinguished peaks.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The spectrum from a cleaned Ni reveals one dominant, asymmetric line shape at 852.5 eV and two broad, less intensive satellite lines (plasmon loss peaks) with binding energies (BE) about 3.0 eV and 6.0 eV above the main line. The same XPS spectra have been previously reported from cleaned Ni surfaces in the literature [7,10], supporting our assumption of efficient cleaning of Ni surfaces within the UHV chamber. After oxidation, the XPS spectra become more complex with several new and well-distinguished peaks.…”
Section: Resultssupporting
confidence: 80%
“…The low-energy oxygen implantation may represent an alternative method for thin oxide-film formation on Ni surfaces. It has been shown previously that ion-bombardment represent an attractive and feasible alternative for oxidation of different metallic and semiconductor surfaces with controlled amount of oxidation and oxide thickness, even at room temperature (RT) [6][7][8][9]. Indeed, in our previous study, we have shown that oxygen bombardment is more efficient in creating thin NiO films on Ni surfaces than oxidation by electrochemical methods [6].…”
Section: Introductionmentioning
confidence: 96%
“…The information about chemical states and atomic bonding in the as-received implant and the implant modified with the alendronate coating was took out from chemical shifts in XPS measurements around core-levels of specific elements. The photoemission spectrum around Ti 2 p core-level measured on the as-received implant ( Figure 3 a) shows a typical structure characteristic for TiO 2 [ 61 , 62 ]. It consists of a spin-orbit doublet with the separation of 5.8 eV between the Ti 2 p 3/2 and Ti 2 p 1/2 peaks and the energy position of Ti 2 p 3/2 line at the BE of 458.5 eV.…”
Section: Resultsmentioning
confidence: 99%
“…XPS was conducted focusing on Ti 2p core-levels to explore the oxidation state of Ti (II, III, or IV for TiO, Ti 2 O 3 , or TiO 2 , respectively). 41,42 The Ti 2p 3/2 photoemission peak at 458.8 eV with the spin−orbit splitting between Ti 2p 3/2 and Ti 2p 1/2 states of ca. 5.7 eV corresponds to the presence of Ti 4+ states from a stoichiometric TiO 2 layer.…”
Section: Resultsmentioning
confidence: 99%